TONOLOGY OF ÈLÓYÌ LANGUAGE - Shehu, Ibrahim Ahmad; Abubakar, Sirajo Muhammad; Jatau , Stephen (International Journal of Arts, Languages, Linguistics and Literary Studies, 2023)
Èlóyì (also known as Afo, Afu, Aho, Èjirí) is a tone language with its own unique syllable structure and tone system. This work is meant to carry out a tonological analysis on Èlóyì language using the auto-segmental approach. Like every other tone language, certain tonal systems may or may not be obtained. Èlóyì, like most West-African languages, operates basically a register tonal system where high, mid, and low tones are all attested. The study reveals that contour tones are also permissible in the language with a few cases of occurrence. A downstepped high tone is somehow also permissible in Afo. The function of tone in Èlóyì cannot be overemphasized as tone functions in Èlóyì to mark pitch on words and express certain grammatical information and to larger extent, distinguish between identical lexical/grammatical categories.